The Effect of Gender Diversity on the Board of Directors and Ownership Structure on Tax Avoidance - Salwa, Ummi Raehanatul; Atikah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this study is to evaluate how gender diversity among board members, managerial ownership, and foreign ownership influence tax avoidance. The research includes two additional control variables, specifically profitability and leverage. The research concentrated on businesses in the Food and Beverage sub-industry that are publicly traded on the Indonesia Stock Exchange (IDX) between 2020 and 2022. A purposive sampling method was utilized to select 111 samples for analysis. The study utilizes panel data regression analysis using the Random Effect Model (REM). The findings indicated that there was no significant impact on tax avoidance from gender diversity on the board of directors and managerial ownership. Subsequently, overseas ownership exerts a notable beneficial impact on tax evasion.